Validation of metacognitive awareness inventory from a private medical university in India - Abirami Omprakash; Archana Prabu Kumar; Maheshkumar Kuppusamy; B W. C. Sathiyasekaran; Thyagarajan Ravinder; Padmavathi Ramaswamy (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Metacognition is the awareness and the capability to regulate one's own thinking process. Metacognition is critical in medical education for clinical reasoning and management. Hence, the objective of this study is to evaluate the construct validity and reliability of the Metacognitive Awareness Inventory (MAI) among first-year medical and dental students, from a private medical university in India, using confirmatory analysis and internal consistency method. MATERIALS AND METHODS: This was a cross-sectional study using convenient sampling. Fifty-two-item MAI was administered to 933 first-year medical and dental students from a private medical university in India. Exploratory factor analysis (EFA), principal component analysis, Cronbach's α, and confirmatory factor analysis with global fit indices were performed. Structural equation modeling (SEM) was performed to evaluate the relationship between the structural path and factors using AMOS version 22. RESULTS: During EFA, 12 items with <0.40 factor loadings were trimmed sequentially. The remaining items with respective factors had a good internal consistency of ≥ 0.9. Comparative fit index (0.78), goodness-of-fit index (0.8), adjusted goodness of fit index (0.77), Tucker-Lewis index (0.7), standardized root mean square residual (0.06), and root mean square error of approximation (0.09) values showed that six-factor model fits to satisfactory. Pearson's correlation coefficient was found to be high between factors (>0.80). SEM for each item (observed) and factor (unobserved) illustrated the hypothesized model. CONCLUSION: The resultant 40-item model based on MAI designed by Schraw is a valid and reliable tool for assessing the metacognitive awareness of Indian students. Employing a valid and reliable tool in assessing the metacognitive awareness will help the academicians in incorporating appropriate curricular interventions.